Implementasi Peran Praktisi Humas dalam Mengkomunikasikan Kinerja Anggota Fraksi PKS DPR RI Jelang Pemilu 2024 - Tri Yoga, Rahmadi; Yugih Setyanto (Fakultas Ilmu Komunikasi Universitas Tarumanagara, 2024)
In carrying out its vision and mission, the The Prosperous Justice Party (PKS) faction in the Indonesian Parliament (DPR RI) necessitates the involvement of public relations to effectively communicate the overall performance of its members to the public. This study aims to explore the role of public relations of the PKS DPR RI faction in socializing the performance of PKS faction members ahead of the 2024 elections. In this study, the author used descriptive qualitative methods and data collection techniques through interviews, non-participant observation, and recording. Based on the findings, the public relations of the PKS DPR RI faction plays a role in helping to communicate all the work of the PKS DPR RI faction in the form of activities, policies, and responses to issues that occur in the public sphere to build public perceptions in a more responsible way, which is assisted by a public relations work system that is integrated with all media expert devices, with outputs in the form of public relations products in the form of releases, photos and videos published to all official faction channels, faction members, and media crew. Technically, ahead of the 2024 election, the Faction's public relations campaign the performance of Faction members by making a recap of the performance of the last four years, which is presented in the form of public relations products, which will then be distributed to all internal and external parties of the Faction, including the media crew. The four indicators of the role of public relations practitioners applied by the public relations of the PKS DPR RI Faction include expert prescriber and communication facility The public relations practitioners of the PKS DPR RI Faction apply four indicators to define their role, which encompasses being an expert prescriber, communication facilitator, problem-solving process facilitator, and communication technician, problem-solving process facilitator, and communication technician. Dalam menjalankan visi dan misinya, Fraksi Partai Keadilan Sejahtera (PKS) DPR RI membutuhkan peran humas untuk mengkomunikasikan seluruh kinerja anggota fraksi kepada masyarakat. Penelitian ini bertujuan untuk mengetahui peran Humas Fraksi PKS DPR RI dalam mensosialisasikan kinerja anggota Fraksi PKS jelang Pemilu 2024. Dalam penelitian ini penulis menerapkan teknik pengumpulan data melalui wawancara, metode deskriptif kualitatif, observasi non-partisipan dan dokumentasi. Berdasarkan temuan, humas Fraksi PKS DPR RI berperan dalam membantu mengkomunikasikan seluruh kerja Fraksi PKS DPR RI berbentuk kegiatan, kebijakan dan menanggapi isu yang terjadi di ruang publik, untuk membangun persepsi publik dengan cara yang lebih bertanggung jawab. Humas dibantu dengan sistem kerja kehumasan yang terintegrasi dengan seluruh perangkat tenaga ahli media, dengan luaran berbentuk produk humas berupa rilis, foto dan video yang dipublikasikan ke seluruh kanal resmi fraksi, anggota fraksi, dan awak media. Secara teknis, jelang pemilu 2024, humas fraksi melakukan kampanye kinerja anggota fraksi dengan membuat rekapitulasi kinerja empat tahun terakhir, yang disajikan dalam bentuk produk humas yang disalurkan ke seluruh pihak internal dan eksternal fraksi. Adapun empat indikator peran praktisi humas yang diterapkan oleh humas Fraksi PKS DPR RI diantaranya penasehat ahli, fasilitator komunikasi, fasilitator proses pemecahan masalah, dan teknisi komunikasi.